THE ELDERS AND THE PREFERENCE OF THE PLACE FOR MEDICAL TREATMENT - Ayoob, S.M. (International Journal of Psychosocial Rehabilitation, 2020)
Ageing is considered as a natural process and a universal phenomenon. The advancement of technology and new scientific revolution lead people to live longer with adequate facilities. Health care centres whether it may be public or private in ownership made available to elders to get treatment to all of their acute and chronic diseases. The study focused on the elderly people and their preference of the place for medical treatment. The study is undertaken in two aspects such as socio-economic profile (age, sex, education, occupation, monthly income and family type) of the elderly respondents as independent variables and places for medical treatment of elderly people as dependent variables. A pre-pilot study was conducted prior to the study. Addalaichenai Divisional Secretariat area in Ampara district of Sri Lanka is selected to carry out this study using a simple random sampling method. To conduct this research successfully both qualitative and quantitative research methods were used in this study. The methods questionnaires survey, key informant interviews and focus group discussions are used to collect primary data. The collected data have been classified and tabulated with the help of statistical software package (SPSS). The chi-square test of independence has also been used for the nominal data in this study. The findings indicated that the respondents choose government hospitals, private clinics, traditional healers/ religious centres and medical shops as a place for medical treatment. Majority 46.6 per cent of the respondents visit the government hospitals. The chi-squire test of independence shows that there is a relationship between age, sex, education, occupation, monthly income and family type of the respondents and the preference of the place for medical treatment.